Аналіз показників якості гальмівних колодок з чавуну і багатокомпонентних композиційних матеріалів - Сіренко, К.А.; Мазур, В.Л. (Physico-technological Institute of Metals and Alloys, 2024)
The properties and performance characteristics of railway brake pads made of cast iron and a multicomponent composite material (rubber-asbestos and asbestos-free rubber mixtures) are considered. Approaches to assessing the force, friction coefficient, and thermal conductivity of brake pads made of different materials in the contact zone with the wheels of railway rolling stock are analysed. The quality indicators of brake pads of different types made of cast iron, composite rubber compound, and composite material with cast iron inserts are compared. It is shown that the coefficients of friction of cast iron pads on the wheel surface are 1.5...2.0 times lower than the coefficients of friction of pads made of composite rubber compound. The main disadvantage of brake pads made of composite rubber compound is the low thermal conductivity of this friction material and, as a result, insufficient heat removal from the contact area between the pad and the wheel of the vehicle. The above fully applies to composite pads with cast iron inserts, which do not help the unsatisfactory situation with heat removal from the friction zone between the pad and the wheels. The dependences of the thermal conductivity coefficient of cast iron with lamellar graphite on its hardness, degree of eutecticity, and carbon equivalent of its chemical composition are considered. It is emphasised that the technical specifications for brake pads made of composite material do not comply with the legislation of Ukraine, since they do not regulate the percentage of rubber compound components and their chemical composition. The standards for cast iron brake pads fully meet the legal requirements for their construction. Foundries in Ukraine have modern equipment and are prepared to manufacture cast iron pads of improved quality, in particular by making them from alloyed and partially graphitised cast iron.